Motivation Relationship Work with Perilku Caring Nurses in Emergency Care Facilities Hospital Priama Nawacita Comes Dave Mahakam Ulu - Hubung Bang; Parellangi Parellangi; Wiyadi Wiyadi (International Journal of Global Sustainable Research, 2023)
Motivation is very closely linked to any action performed by a nurse in caring behavior. Nursing is a professional service, an integral part of home health care. The success of a hospital in carrying out its functions is characterized by the quality of service provided by the hospital. Objective: To find out the relationship between the motivation of work and the behavior of the nurse in the Emergency Care Facility of the Hospitals Priama Nawacita Datah Dave Mahakam Ulu. The research design on this study is observational using a cross-sectional approach. The research was conducted in February 2023. The population in this study is the whole of the nurses who work in the Emergency Care Facility of the Hospital Priama Nawacita Datah Dave Mahakam Ulu amounting to 20 people. Sample determination using total sampling. The statistical tests used are Chi Square. The results have been linked to the motivation of work with the behavior of nurses in the Emergency Care Facility of the Hospital Priama Nawacita Datah Dave Mahakam Ulu.